An assessment of the small-scale fisheries in the Kogelberg district of the Western Cape, South Africa - Jordan, Tia (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2016)
Small-scale fisheries play a critical role in communities by contributing to food security, poverty alleviation and source of income. The study focused on the Kleinmond small-scale fishery and estimated the current economic value of the fishery as well as exploring the potential for increasing this and also whether it is being used in a way that ensures sustainable harvesting of the marine resources. It was important to evaluate the ecological, economic and social dimensions of the fishing community in order to address the problems currently facing the community. The study draws on previous research done in the Kleinmond area. Data were collected to update and complement previous research and addresses current research. In order to investigate the fisheries catch contribution in the area, data were obtained from the Department of Agriculture, Forestry and Fisheries. Three different questionnaires were developed and conducted in face-to-face formal and informal interviews with the various stakeholders (n=42) in the value-chain. Interviews were also conducted telephonically with other stakeholders and a focus group was formed to supplement previous available data. Simple economic models were developed for the fisheries working from the Kleinmond harbour, which were used to estimate the gross and net economic value of catches for individual right-holders, as well as the Kleinmond area as a whole. The economic models used in this study showed that the West Coast rock lobster Jasus lalandii, fishery was the primary source of income for small-scale fishers. This was due to the rock lobsters being sold to the export market as a high-valued commodity, whereas the linefish were sold to the local market as a lower-valued commodity. However, linefish were found to be more of a commodity to the community as a portion would be retained for personal consumption. The linefishers were concerned in that over the past couple of years, snoek Thrysites atun have been absent the Kleinmond area, resulting in and the fishing effort shifting to a resident species Cape bream Pachymetopon blochii. Whereas West Coast rock lobster were considered to be harvested sustainably under the current total allowable catch strategy, there was concern for the future of the fishery because of the occurrence of illegal fishing, both locally and nationally. Small-scale fisheries in the Kleinmond community are largely dependent on fishing resources, even though the industry is only marginally profitable. Future management measures should concentrate on optimising the value-chain to provide both sustainability for the resources and improve the livelihoods of the community.
Keywords: Uncatalogued